STATE AND CONSTITUTION IN THE PERSPECTIVE OF PANCASILA: A STUDY OF CONSTITUTIONALISM, THE 1945 CONSTITUTION, AND THE INDONESIAN CONSTITUTIONAL SYSTEM - Bambang Yuniarto; Najwa Nihayah; Lailatul Maulida; Mohammad Dahlan Antasya; Muhammad Yazid Agil; Mohammad Dhafa Abduh Jalal (International Journal of Teaching and Learning, 2025)
The constitution plays a fundamental role as the supreme law governing the structure and limitations of state power. In the context of Indonesia, the 1945 Constitution (UUD 1945) is the primary foundation, which is inseparable from the philosophical meaning of Pancasila. Pancasila holds a central position as the "source of all sources of law," binding the entire legal architecture and state practices. This research aims to provide an understanding of the systematic integration between Pancasila's values and the principles of constitutionalism within the Indonesian constitutional system. It focuses on understanding constitutionalism within the framework of Pancasila, the position of the 1945 Constitution, and the extent to which Pancasila's principles strengthen modern state governance practices. This research uses a qualitative approach with literature study and normative legal research methods. The data used includes the 1945 Constitution, Constitutional Court decisions, and academic literature. Analysis was conducted through qualitative content analysis to examine the internalization of Pancasila's values within the formal constitutional framework. The results show that Pancasila functions as a living philosophical foundation for the 1945 Constitution and the Indonesian constitutional system. Indonesian constitutionalism is a synthesis of universal values with the values of divinity, humanity, and social justice. Constitutional reforms post-1998 have strengthened the constitutional system, particularly the check and balance mechanisms. The actualization of Pancasila's values still faces challenges, such as interpretative ambiguity and inconsistencies between formal norms and practices in the field. Pancasila must be the primary reference in public policy formulation and state governance practices.